Prevention and Control of Aflatoxin and associated losses during post harvest handling of agricultural commodities in EAC. - EAC (EAC, 2018)
Aflatoxins are a set of poisonous substances produced by fungi (molds) that can potentially cause cancer and contribute to stunting and immunosuppression in vulnerable groups. Aflatoxin contamination occurs in major staple crops in East Africa, such as maize, rice and sorghum.
Pages 3, includes tables and bibliographical references.
Keywords: Aflatoxin